(untitled) (Journal of Economic Research & Business Administration, 2016)
Kazakhstan stands today on the border of the new stage socially to economic modernization and political democratization. Only at presence of modern competitiveness and market open economy, unreserved scopes only raw material sector, based on respect and defense of private ownership and contract relations, initiative and enterprise of all members of society, it maybe to heave up the economy of country on the level of world standards. Strategy of industriallyinnovative development of Kazakhstan is sent to realization of active scientific and innovative politics with the purpose of stimulation of enterprise on organization of competitive and exported productions. Thus control system of competitiveness of managing subjects from position of innovative approach must provide transformation of technical and technological possibilities in competitive edges.